Studi Kelayakan Perlintasan Sebidang antara Jalan Kereta Api dengan Jalan Raya - Aswad, Yusandy (Department of Civil Engineering, Diponegoro University, 2013)
Development of road transport facilities very often forms a junction with railway transportation. Accidents between motor vehicles and railway crossings often occur on a level crossing. Purpose of this study is to provide recommendations plot proper of crossings according to Ministerial Decree No.53 of 2000 between the railways to the highway. Feasibility of level crossing can be observed from the speed of trains, the headway between trains that pass on a level crossing, highway class, alinment position. From analysis is seen level crossing feasible because it met the requirements: a single-speed railway with the next train passing by < 60 km/h, the time interval (head way) between trains one by one with the train and the next train passing on the location of more than six minutes, the highway is a road passing is highway class III A and not located on railroad arch over the street corner.